Transcriptomic analysis reveals differentially expressed genes and a unique apoptosis pathway in channel catfish ovary cells after infection with the channel catfish virus. Issue 71 (December 2017) - Dawar, Farman Ullah; Hu, Xianqin; Zhao, Lijuan; Dong, Xingxing; Xiong, Yang; Zhou, Meng; Liang, Rishen; Sarath Babu, V.; Li, Jun; Mei, Jie; Lin, Li
Abstract: The channel catfish virus (CCV) can cause lethal hemorrhagic infection in juvenile channel catfish, thereby resulting in a huge economic loss to the fish industry. The genome of the CCV has been fully sequenced, and its prevalence is well documented. However, less is known about the molecular mechanisms and pathogenesis of the CCV. Herein, the channel catfish ovary cells (CCO) were infected with CCV and their transcriptomic sketches were analyzed using an RNA sequencing technique. In total, 72, 686, 438 clean reads were obtained from 73, 231, 128 sequence reads, which were further grouped into 747, 168 contigs. These contigs were assembled into 49, 119 unigenes, of which 20, 912 and 18, 333 unigenes were found in Nr and SwissProt databases and matched 15, 911 and 14, 625 distinctive proteins, respectively. From these, 3641 differentially expressed genes (DEGs), comprising 260 up-regulated and 3381 down-regulated genes, were found compared with the control (non-infected) cells. For verification, 16 DEGs were analyzed using qRT-PCR. The analysis of the DEGs and their related cellular signaling pathways revealed a substantial number of DEGs that were involved in the apoptosis pathway induced by CCV infection. The apoptosis pathways were further elucidated using standard apoptosis assays. The results showed that CCV could induce extrinsic apoptosis pathway (instead of a mitochondrial intrinsic apoptosis pathway) in CCO cells. This study helps our understanding of the pathogenesis of CCV and contributes to the prevention of CCV infection in channel catfish. Highlights: The transcriptomic sketches of CCO cells were analyzed after CCV infection. Thousands of genes in CCO cells were involved against CCV infection. The apoptosis caused by CCV infection in CCO cells was observed. The CCV infection could induce extrinsic apoptosis pathway in CCO cells.